Penyuluhan Program Pencegahan Bullying di LKSA di Yayasan Pendidikan dan Penyantunan Anak Yatim Addinu waddun’ya - Nanda, Marshellino Aurelio; Saputra, Kintan Nabilah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
This article discusses efforts to prevent bullying at the Child Social Welfare Institution (LKSA) carried out by students of the Faculty of Law, UPN "Veteran" Jawa Timur. Bullying is any form of oppression or violence committed continuously by one person or a group of stronger individuals against another person with the intent to harm. The article identifies forms of bullying, such as verbal, physical, social, and cyberbullying, and outlines the characteristics of victims and perpetrators of bullying. Additionally, it discusses the negative impacts of bullying on victims, such as loss of self-confidence, trauma, and depression, as well as preventive and repressive measures to address bullying. This study aims to raise awareness and provide effective strategies for creating a safe and respectful environment at LKSA.